Determinants of in-house food ordering application success: Empirical evidence from restaurant X - Sulistiowati; Junaid Yousaf; Titik Lusiani; Yosef Richo Adrianto; Nunuk Wahyuningtyas (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
Restaurant X faces the challenge of low self-ordering application adoption compared to third-party platforms, despite implementing an omnichannel strategy. This study aims to evaluate the success of the application's adoption using the DeLone & McLean model. A quantitative method was employed, involving 115 respondents, and analyzed using Structural Equation Modeling (SEM-PLS). The model examines the impact of system quality, information quality, and service quality on use, user satisfaction, and perceived usefulness. The results indicate that information quality and system quality significantly influence both use and user satisfaction (p < 0.05). Conversely, service quality has no significant effect (p > 0.05), suggesting that users prioritize technical stability and data accuracy over personal service support within the self-owned application context. Use and satisfaction were found to significantly enhance perceived usefulness. Predictive Relevance (Q2) values ranging from 0.616 to 0.667 confirm the model's solid predictive power. The study concludes that the application's success depends heavily on technical reliability and product information accuracy. Management is advised to prioritize system stability and real-time data updates to improve the application's competitiveness against rival platforms.